ANALISIS RANTAI NILAI TEPUNG KELAPA PADA PT. TROPICA COCOPRIMA - Hamni ., Pisalemo; Nordy F. L. Waney; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the value of coconut flour at PT. Tropica Cocoprima. This research has been conducted at PT. Tropica Cocoprima and actors in its supply chain located at Jalan Trans Sulawesi Lelema Village Tumpaan Subdistrict of South Minahasa Regency. The type of data used is primary data and secondary data. Sources of data were obtained through interviews using questionnaires containing questions related to this study. The sampling method is Purvosive Sampling and the sample is PT. Tropica Cocoprima as focal firm and suppliers of raw materials as many as 5 suppliers as well as coconut farmers as much as 2 farmers taken from each supplier. The method of analysis used in this research is value chain analysis with cost and margin approach. Based on the research results can be concluded that the value chain of coconut flour at PT. Tropica Cocoprima There are several actors involved in the process of value creation. The actors involved are coconut farmers and suppliers who bring raw materials to PT. Tropica Cocoprima. The actors involved in the value chain of coconut flour each earn a margin that corresponds to the effort that has been done. Coconut flour value chain at PT. Tropica Cocoprima from one, two and three actors experienced value increase is Rp.195.000.000. Margin received by PT. Tropica Cocoprima amounting to Rp.12.277.822 then the supplier obtained a margin of Rp.6,675,000 and the farmer earned a margin of Rp.100.102.700.